Down-regulation of pancreatic and duodenal homeobox-1 by somatostatin receptor subtype 5: a novel mechanism for inhibition of cellular proliferation and insulin secretion by somatostatin - Zhou, Guisheng; Sinnett-Smith, Jim; Liu, Shi-He; Yu, Juehua; Wu, James; Sanchez, Robbi; Pandol, Stephen J.; Abrol, Ravinder; Nemunaitis, John; Rozengurt, Enrique; Brunicardi, F. Charles (Frontiers in Physiology, 2014)
Somatostatin is a regulatory peptide and acts as an endogenous inhibitory regulator of the secretory and proliferative responses of target cells. Somatostatin’s actions are mediated by a family of seven transmembrane domain G protein-coupled receptors that comprise five distinct subtypes (SSTR1-5). SSTR5 is one of the major SSTRs in the islets of Langerhans. Homeodomain-containing transcription factor pancreatic and duodenal homeobox-1 (PDX-1) is essential for pancreatic development, β cell differentiation, maintenance of normal β cell functions in adults and tumorigenesis. Recent studies show that SSTR5 acts as a negative regulator for PDX-1 expression and that SSTR5 mediates somatostatin’s inhibitory effect on cell proliferation and insulin expression/excretion through down-regulating PDX-1 expression. SSTR5 exerts its inhibitory effect on PDX-1 expression at both the transcriptional level by down-regulating PDX-1 mRNA and the post-translational level by enhancing PDX-1 ubiquitination. Identification of PDX-1 as a transcriptional target for SSTR5 may help in guiding the choice of therapeutic cancer treatments.